PHYSIOLOGICAL EFFECTS OF THE INTRODUCING OF THE PROGRAM OF PERSONALIZED SUPPORT FOR ADOLESCENT CHESS PLAYERS - А.А. Semchenko; Mamylina, N.V.; Korchemkina, Yu.V.; Savchenkov, А.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the physiological effects of introducing a program of personalized support into the educational and training process of 15-16 year old chess players. Methods and structure of the study. The experiment involved 15 teenage chess players (15-16 years old) with 1-2 sports categories. The functional assessment of the respiratory and cardiovascular systems was carried out using the Stange and Genchi tests, the calculation of the endurance coefficient, and the fatigue state index. The quantitative assessment of the health of chess players was studied according to the method developed by N.N. Mityukov on the basis of changes in the level of adaptive potential. A comparative five-segment analysis of body composition indicators was carried out using professional Tanita BC-418MA analyzer scales (Japan). Research results and conclusions. A personalized program of physical training of a chess player is proposed. A feature of the personalized support program for a chess player is that it includes the creation of a training system taking into account individual indicators of physical endurance with entry into the database and the implementation of professional consultations in the pre-competitive and post-competitive period. After the application of the personalized physical training program, the reserve capacity, the efficiency of the functioning of the respiratory and cardiovascular systems of chess players increased.